FORMULATION, EVALUATION OF PHYSICAL PROPERTIES AND ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT AND ETHYL ACETATE FRACTION GEL OF Moringa oleifera LEAVES - Annisa Fatmawati; Rizal Fauzi; Adhi Gunawan; Riza Kurniawati; Depita Sucianingsih; Sain Abrari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2022)
The leaves of Moringa (Moringa oleifera Lam) contain quercetin, a flavonoid that plays a role in the skin regeneration process with an antioxidant mechanism, can play a role in the healing process of skin wounds. The ethanol extract of Moringa leaves was fractionated using petroleum ether and ethyl acetate. The MLEE (Moringa leaf ethanolic extract) gel formula was made to vary the extract weights in the order of 2%, 4% and 6% (b/b), while EFML (Moringa leaf ethyl acetate fraction) gel preparations were made to vary the extract weights in the order of 1%, 2% and 4% (b/b). Evaluation of the physical properties of the gel preparations, including organoleptic observation, homogenity tests, pH measurements, spreadability tests, adhesion tests, and antioxidant activity using the DPPH method. The physical properties of all preparation fulfill the requirements. The test for antioxidant gel MLEE IC50: MLEE 1 144.72 ± 3.52 ppm; MLEE 2 138.15 ± 0.93 ppm; MLEE 3 136.59 ± 1.68 ppm when compared to extracts IC50 MLEE 23.14 ppm (very strong antioxidant activity). The EFML gel formulation (IC50: EFML 1 208.81 ± 4.09 ppm; EFML 2 193.22 ± 2.53 ppm; EFML 3 182.48 ± 2.11 ppm) gave the same results when compared to the thick fraction of Moringa leaves, which has moderate antioxidant activity. The formula gel MLEE 3 has moderate antioxidant activity, which is the best gel formulation based on the results of physical properties test.